Wedgieman : a hero is born - Harper, Charise Mericle (Step into reading. Step 3, 2012)
Veggieboy practices flying, lifting, and helping people to hone his superhero skills, and finally Veggieman's training as a superhero is complete, but he is surprised when children want to change his name.